Nasal Anatomy of the Non‐mammaliaform Cynodont Brasilitherium riograndensis (Eucynodontia, Therapsida) Reveals New Insight into Mammalian Evolution. Issue 11 (November 2014) - Ruf, Irina; Maier, Wolfgang; Rodrigues, Pablo G.; Schultz, Cesar L.; Van Valkenburgh, Blaire; Smith, Timothy; Craven, Brent; Laitman, Jeffrey T.
ABSTRACT The mammalian nasal cavity is characterized by a unique anatomy with complex internal features. The evolution of turbinals was correlated with endothermic and macrosmatic adaptations in therapsids and in early mammals, which is still apparent in their twofold function (warming and moistening of air, olfaction). Fossil evidence for the transformation from the nonmammalian to the mammalian nasal cavity pattern has been poor and inadequate. Ossification of the cartilaginous nasal capsule and turbinals seems to be a feature that occurred only very late in synapsid evolution but delicate ethmoidal bones are rarely preserved. Here we provide the first µCT investigation of the nasal cavity of the advanced non‐mammaliaform cynodont Brasilitherium riograndensis from the Late Triassic of Southern Brazil, a member of the sister‐group of mammaliaforms, in order to elucidate a critical anatomical transition in early mammalian evolution. Brasilitherium riograndensis already had at least partially ossified turbinals as remnants of the nasoturbinal and the first ethmoturbinal are preserved. The posterior nasal septum is partly ossified and contributes to a mesethmoid. The nasal cavity is posteriorly expanded and forms a distinctive pars posterior (ethmoidal recess) that is ventrally separated from the nasopharyngeal duct by a distinct lamina terminalis. Thus, our observations clearly demonstrate that principal features of the mammalian nasal cavity were already present in the sister‐group of mammaliaforms. Anat Rec, 297:2018–2030, 2014. © 2014 Wiley Periodicals, Inc.